Isolated Metastatic Malignant Melanoma of the Right Inguinal Lymph Node with Unknown Primary Lesion - Das, Debasish; Paul, Deb Prosad; Iqbal, Kazi Sohel (Journal of Enam Medical College, 2018)
Malignant melanoma develops from the pigment containing cells known as melanocytes. Melanoma is more common in men than in women. It is found typically in the skin. It is also found in the mouth, intestine, eye and other sites. Melanoma may develop from a mole with changes including an increasing in size, irregular edges, changes in color, itchiness or skin breakdown. Prognosis is poor if it is not treated early. The primary cause of melanoma is UV light exposure. Patients with history of affected family members and poor immune function are at greater risk. Diagnosis is by biopsy from any affected skin lesion. Recurrence is common even many years after the initial diagnosis. Here we present a case of malignant melanoma of the inguinal lymph node with unknown primary lesion. Surgery was done with complete excision of inguinal lymph node. Biopsy report showed metastatic malignant melanoma. J Enam Med Col 2018; 8(3): 174-176